Tax literacy and tax awareness of salaried individuals in Sabah and Sarawak / Amrizah Kamaluddin and Nero Madi - Kamaluddin, Amrizah; Madi, Nero (Faculty of Accountancy, 2005)
The central issue of this study is to gauge the general level of tax literacy among salaried taxpayers in Sabah and Sarawak. This study is undertaken to shed light on our preparedness to face the challenge posed by the implementation of Self Assessment System (SAS) on salaried tax payers beginning from the year 2004 where taxpayers are expected to be functionally literate to compute their own tax liabilities accurately. For the purpose of this study, samples were randomly taken from salaried taxpayers working in the main cities in Sabah namely Sandakan, Tawau and Kota Kinabalu and Sarawak which were Kuching, Sibu, Bintulu and Miri. Statistical test using One-Way ANOVA was applied on the mean tax literacy scores by place of work. Relationships between tax literacy scores and place of work were also analyzed by using the Chi-square test of independence. Some of the findings, among others, indicated that salaried taxpayers in Sarawak were found to be more tax literate compared to their counterparts in Sabah. It was also discovered that the sector of employment is not an important factor of tax literacy. Public and corporate sector employees were found to be equally literate as indicated by insignificant difference in the mean scores of these two sectors. Overall, it could be inferred that salaried taxpayers in both states are not prepared for SAS in 2004 as reflected by a low percentage of 'very literate' category.